An in vitro study to compare the transverse strength of thermopressed and conventional compression-molded polymethylmethacrylate polymers - Anjana Raut; Polsani Laxman Rao; BVJ Vikas; T Ravindranath; Archana Paradkar; G Malakondaiah (Wolters Kluwer Medknow Publications, 2013)
Statement of Problem: Acrylic resins have been in the center stage of Prosthodontics for more than half a century. The flexural fatigue failure of denture base materials is the primary mode of clinical failure. Hence there is a need for superior physical and mechanical properties. Purpose: This in vitro study compared the transverse strength of specimens of thermopressed injection-molded and conventional compression-molded polymethylmethacrylate polymers and examined the morphology and microstructure of fractured acrylic specimens. Materials and Methods: The following denture base resins were examined: Brecrystal (Thermopressed injection-molded, modified polymethylmethacrylate) and Pyrax (compression molded, control group). Specimens of each material were tested according to the American Society for Testing and Materials standard D790-03 for flexural strength testing of reinforced plastics and subsequently examined under SEM. The data was analyzed with Student unpaired t test. Results: Flexural strength of Brecrystal (82.08 ± 1.27 MPa) was significantly higher than Pyrax (72.76 ± 0.97 MPa). The tested denture base materials fulfilled the requirements regarding flexural strength (>65 MPa). The scanning electron microscopy image of Brecrystal revealed a ductile fracture with crazing. The fracture pattern of control group specimens exhibited poorly defined crystallographic planes with a high degree of disorganization. Conclusion: Flexural strength of Brecrystal was significantly higher than the control group. Brecrystal showed a higher mean transverse strength value of 82.08 ± 1.27 MPa and a more homogenous pattern at microscopic level. Based on flexural strength properties and handling characteristics, Brecrystal may prove to be an useful alternative to conventional denture base resins.